Digital payments during the COVID-19 pandemic in Poland: An initial insight on the consumer perception of security and convenience - Bednarz, Joanna; Markiewicz, Magdalena; Szmelter-Jarosz, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2024)
Purpose/Research problem – The paper’s key purposes are twofold: first, to identify the most important determinants for using mobile payments in the initial phase of the COVID-19 pandemic when the rules and behaviour changed; second, to investigate whether and why the coronavirus pandemic increased the degree of digital payments usage. Design/Methodology/Approach – The aim of the survey was to capture the ‘fresh’ effect of restrictions imposed by the government in Poland regarding digital payments. The research data were obtained in the CAWI survey after the pandemic started and before the end of the first wave to assess the result just for that period. Results – The study proved that the first phase of the COVID-19 pandemic increased the degree of mobile payments usage due to the prevailing sense of uncertainty. The pre-pandemic preferences of buyers towards the cost, convenience, and risk have changed. In the initial phase of the pandemic, perceived personal security was extended and covered not only transaction security, but also health safety with benefits resulting from avoiding touching the banknotes and maintaining social distancing. This was identified as more important than perceived convenience and costs. Originality/Value – The time of the analysis time was a kind of a ‘research window’, when the researchers and respondents were exposed to the first wave of the pandemic and did not have a foresight of the coming waves of virus transmission. The questions concerning the sum and quantity of spending were adjusted to the time of quasi-stability in the economy – after the previous crisis and before the inflation level rose in the subsequent waves – which was mainly the effect of the monetary policy response to lockdowns.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 115-144